Mechanical ventilation with the esophageal tracheal combitube (ETC) in the intensive care unit. Issue 4 (December 1987) - Frass, M; Frenzer, R; Mayer, G; Popovic, R; Leithner, C
Abstract : Mechanical ventilation in critically ill patients is usually performed with the conventional endotracheal airway. The esophageal tracheal combitube (ETC) is a new device for cardiopulmonary resuscitation, conceived to bridge the gap between hospital and prehospital phases. The ETC may be used in esophageal and endotracheal positions. The authors report six patients who were ventilated with the ETC in the esophageal obturator position for 2-8 h after emergency ventilation. Blood gas data showed adequate ventilation with the ETC during the observation period. Data suggest that mechanical ventilation with the ETC is possible for several hours after cardiopulmonary resuscitation. This might be helpful during the initial post-arrest period, when replacement of the ETC by a conventional endotracheal airway might destabilize a vulnerable patient.